TRA-1-60-positive/CD45low cells found in the peripheral blood of prostate cancer patients with metastatic disease – A proof-of-concept study. Issue 1 (January 2020) - Schäfer, Claudia; Ju, Yawen; Tak, Youngbin; Vazquez, Cesar; Han, Sangyoon J.; Tan, Edwin; Shay, Jerry W.; Holmqvist, Mats; Danuser, Gaudenz; Schopperle, William M.; Bubley, Glenn
Abstract: Purpose: Over 90% of all cancer related deaths are due to metastasis. However, current diagnostic tools can't reliably discriminate between invasive and localized cancers. Patients and methods: In this proof-of-concept study, we employed the embryonic stem cell marker TRA-1-60 (TRA+) to identify TRA + cells within the blood of prostate cancer patients and searched for TRA + cells in men with metastatic and localized cancers. We isolated whole peripheral blood mononuclear cells from 26 metastatic prostate cancer patients, from 13 patients with localized prostate cancer and from 17 healthy controls. Cells were stained for DAPI, CD45 and TRA + by immunofluorescence and imaged by epi-fluorescence microscopy. Imaged-based software was used both to identify TRA + cells, and to analyze CD45 levels in TRA+ and negative cells. Results: We found high numbers of TRA + cells within the blood of metastatic cancer patients, whereas healthy individuals or men with localized prostate cancer showed none or very low numbers of TRA + cells. Further analysis of the CD45 levels of TRA + cells revealed a small population of TRA + cells with almost undetectable CD45 levels that were found frequently in metastatic prostate cancer patients. By excluding CD45 positive cells from the TRA + cell pool, we were able to refine the assay to be highly specific in identifying men with metastatic disease. In fact, the difference of CD45 levels between TRA+ and negative cells was a robust measure to distinguish between men with localized and metastatic prostate cancers in this small patient cohort. Conclusions: The data suggest that metastatic prostate cancer patient have significant numbers of TRA+/CD45 low cells which might represent a potential tool for diagnostic assessment in the future. Abstract : Oncology, Cancer research, Cancer; Diagnostics; TRA-1-60; Metastasis; Embryonic stem cells.